'This Situation Can Be Duplicated': Text as Radical Placemaking Tool. - Bickers, George Francis (Palgrave Macmillan, 2019)
The author leads the charge by exploring how "thinking the urban" has important ramifications for spatial practice and lived urban experience. He does so-inspired by the spatial theories of Edward Soja-through an investigation of how fictional literature set in Los Angeles functions as a palimpsestual map of the urban, sometimes with the effect of reinforcing hegemonic conceptions, sometimes helping to subvert them.
Keywords: Stadtforschung; Stadttheorie; Konflikt; Raumbezug; Urbanität; Literatur